The influence of natural factors on poverty in West Halmahera - Permatasari, Dewi; Maski, Ghozali; Susilo, Susilo; Manzilati, Azfi (Edelweiss Applied Science and Technology, 2024)
Poverty remains one of the persistent social issues faced by governments in many regions, including coastal and small island communities. The poverty experienced in these areas is driven by a combination of natural, social, and economic factors. Dynamic environmental conditions, such as seasonal changes, extreme weather, wide geographic dispersion between sea and land, isolation due to limited accessibility, and vulnerability to natural disasters, often trap coastal populations in a cycle of poverty. Data from West Halmahera Regency indicates that poverty levels have shown little improvement up until 2023. This research focuses on a sample of 390 poor residents from the region, utilizing Confirmatory Factor Analysis (CFA) and Principal Component Regression Analysis (PCRA) to examine the factors affecting poverty. The findings reveal that within the Natural Capital variable (X1), the most significant indicators are the distance from the house to a clean water source (X4), with a coefficient of 0.894, the condition of the water source near the residence (X5), with a coefficient of 0.884, and accessibility to clean water sources (X3), with a coefficient of 0.89. West Halmahera, being a coastal and mountainous region, suffers from an unequal distribution of essential infrastructure, particularly in areas far from the district capital. Clean water infrastructure remains absent in many areas, and even in mountainous regions where water piping exists, geographic challenges hinder functionality. Addressing these issues requires collaboration between local governments, the private sector, universities, and the community. Solutions may include programs that incorporate local wisdom and focus on infrastructure development, sustainable water management, and environmentally friendly practices. Such initiatives could enhance access to clean water, improve the local economy, and ultimately reduce poverty in West Halmahera.